Reflections on Calgary’s Spatial Structure: An Urban Economist’s Critique of Municipal Planning in Calgary - Richard Arnott (The School of Public Policy Publications, 2015)
Affordable housing and a manageable commute are central to the well-being of Calgarians. Yet among larger Canadian metropolitan areas today, Calgary already has close to the most expensive housing, and the average journey-to-work time, close to 30 minutes, is as high today as it was in Los Angeles in 2000, when Los Angeles had a population 10 times larger. Decisions around how Calgary grows are based on the policies within The City’s Municipal Development Plan and the Calgary Transportation Plan, which together provide a blueprint for Calgary’s spatial development and transportation system. These plans— and therefore, their assumptions about future effects on congestion and rents — are based around a population forecast that does not reflect the historical growth pattern of the city and legitimizes spatial containment. The shortcomings in these plans, both adopted in 2009, are likely to result in longer commuting times and even more expensive real estate prices. These will be well beyond what The City has prepared citizens to expect and accept, as planners plow ahead with proposals to further entrench the downtown as the dominant employment centre. Calgarians need to be levelled with about the realities that come with pursuing a plan that calls for spatial containment and intensification centred on a single, dominant central business district. The plans present a vision of the “Good Urban Life,” and propose to enforce it through a particular choice of transportation system, through land-use regulation, and through a downtown parking freeze, with little regard to economics. The cost of this vision will in turn discourage new firms and new people from moving to Calgary. Calgarians should be informed about future transportation costs – for mass transit and automobiles – in congestion, time, and funding. And they must be informed about the effects this will all have on the cost of property for families and businesses. Only then can citizens properly consider their options and choose their city’s future. Without that Calgarians may find their quality of life diminished in ways they were never prepared to expect.